(untitled) (Marketing Journal, 2025)
The article analyzes the economic foundations and efficiency of the construction materials industry in Uzbekistan with an emphasis on resource -saving technologies. Based on 2015 –2024 data, the study identifies trends in production growth, reduced energy co nsumption, and increased labor productivity. The findings indicate that a 15% reduction in energy use and a rise in recycled raw materials contribute to lower production costs and higher profitability for enterprises.